The Assessment of Comprehensive Care for Autistic Children Provided by Polish Primary Healthcare Physicians in Parental View - Patryk Domarecki MD; Katarzyna Plata-Nazar PhD (SAGE Publishing, 2024)
Objectives . Important factor in caring for ASD patients is the successful cooperation between the physician and the parent. Methods . The online survey has been conducted. For statistical analysis the t -student test and the U -Mann Whitney test were performed to compare 2 variables, then the Kruskal-Wallis test or ANOVA as well as The Pearson correlation and Sperman's rank correlation were performed. Results . 80.5% of respondent's PHPs did not notice the child's developmental difficulties. 22.02% of respondents can speak to their PHP about a child's difficulties. PHPs take different strategies to make patient contact with the healthcare system easier. We discovered statistically significant differences in the assessment of PHPs' abilities depending on the physicians' specialty, the children's age, the age at ASD diagnosis. Conclusion . The care for autistic patients provided by Polish PHPs is insufficient and the topic needs to be addressed immediately.